Liga Seluler: Pergeseran Olahraga Elektronik ke Peranti Seluler dalam Kompetisi Mobile Legends: Bang Bang di Indonesia - Haryo P Jiwandono; Edeliya Relanika Purwandi (Jurnal Media dan Komunikasi Indonesia, 2020)
In 2010’s, the mobile devices proliferation in Northeast Asia raised the digital mobile games popularity and developed mobile culture technology that supported the flourishment of socio-technical environment in the mode of production, distribution and participation of digital game users in the region to the next level. At the end of 2010, Mobile Legend: Bang Bang became the well-known online game, which was played in mobile devices in Indonesia. The Indonesian Mobile Legend: Bang Bang trend encouraged the participation of e-sport athletes to compete in the Mobile Legend: Bang Bang competition because of becoming more profitable for its users. This trend shows an interesting phenomenon to be studied. This research paper aims to study the dynamics of Mobile Legend: Bang Bang e-sports competition using traditional socio-technical approaches in the field of communication science. This approached used to observe the individual and/or group meaning based on their interaction within Mobile Legend: Bang Bang e-sport community. This research was conducted in the same time period with Kratingdaerng E-Sports Championship on September 2018.